Evolution of clitellate phaosomes from rhabdomeric photoreceptor cells of polychaetes - a study in the leech Helobdella robusta (Annelida, Sedentaria, Clitellata) - Döring, Carmen; Arendt, Detlev (Frontiers in zoology, 2013)
In Annelida two types of photoreceptor cells (PRCs) are regarded as generally present, rhabdomeric and ciliary PRCs. In certain taxa, however, an additional type of PRC may occur, the so called phaosomal PRC. Whereas the former two types of PRCs are always organized as an epithelium with their sensory processes projecting into an extracellular cavity formed by the PRCs and (pigmented) supportive cells, phaosomes are seemingly intracellular vacuoles housing the sensory processes. Phaosomal PRCs are the only type of PRC found in one major annelid group, Clitellata. Several hypotheses have been put forward explaining the evolutionary origin of the clitellate phaosomes. To elucidate the evolution of clitellate PRC and eyes the leech Helobdella robusta, for which a sequenced genome is available, was chosen.